Analysis of Code-Mixing in Multilingual Hospitality Settings - Lia Juniari, Ni Putu; Putra, Eka Dwi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 32 No 1 (2025): MaretDO - 10.24843/ling.2025.v32.i01.p03, 2025)
This study investigates the use of code-mixing by the Front Office Department staff at Ashyana Candidasa Beach Resort, focusing on the functions and types of code-mixing within a multicultural hospitality environment. The primary aim of this research is to identify and categorize the types of code-mixing used by the staff and to assess how these practices contribute to effective communication and improved service. The study employs a qualitative approach, collecting data through observations and interviews with front office staff and guests. The findings reveal that intra-sentential code-mixing is the most common practice, allowing staff to integrate multiple languages within a single sentence. Additionally, code-mixing is used to address various communication needs, such as providing clear instructions, enhancing politeness, handling requests, and managing payment and booking issues. The research highlights the significance of strategic code-mixing in a multilingual setting and recommends language training programs for staff to enhance communication efficiency and guest satisfaction